2007
DOI: 10.1176/appi.ajp.2007.06101664
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mental Health Court in Reducing Criminal Recidivism and Violence

Abstract: The results indicate that a mental health court can reduce recidivism and violence by people with mental disorders who are involved in the criminal justice system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
217
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(235 citation statements)
references
References 29 publications
13
217
1
3
Order By: Relevance
“…Existing data suggest that MHC participation can reduce risk of criminal recidivism (11)(12)(13)(14)(15)(16), although not all studies support that conclusion (17,18). Little research has investigated the effectiveness of MHCs specifically for reducing risk of violence, a gap in the literature that may be related to the fact that early MHCs typically were restricted to persons charged with nonviolent misdemeanors (9,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data suggest that MHC participation can reduce risk of criminal recidivism (11)(12)(13)(14)(15)(16), although not all studies support that conclusion (17,18). Little research has investigated the effectiveness of MHCs specifically for reducing risk of violence, a gap in the literature that may be related to the fact that early MHCs typically were restricted to persons charged with nonviolent misdemeanors (9,17).…”
mentioning
confidence: 99%
“…One study directly examined the effectiveness of an MHC with higher-risk clients in reducing risk of violence by using a retrospective observational design. The study examined criminal justice outcomes of the San Francisco MHC (called the Behavioral Health Court) by using records from local court and jail systems (13). Of the 172 individuals who entered the court during the study, 63% had been charged with felony offenses.…”
mentioning
confidence: 99%
“…At follow-up, both groups reported improved outcomes, although this was not statistically significant. This suggests that those clients who participated in the CJLD service did not experience the structured support and monitoring considered necessary to effect significant changes in their psychosocial health and well-being (Cosden et al, 2005;McNiel & Binder, 2007). This is borne-out by follow-up data which found that only seven (24%, 7/29) CJLD service participants reported acting upon the advice they had received from the CJLD service.…”
Section: Results Results Resultsmentioning
confidence: 99%
“…The lack of any significant change at follow-up is not unexpected perhaps, in that the ability of a CJLD service to effect change on a 'chronic' condition such as alcohol abuse is questionable, given that its primary role is to direct people toward existing services. For example, current service provision in NI is based largely on a Reassuringly perhaps, the levels of reported drug use in both groups were lower than those reported elsewhere (McNiel & Binder, 2007;James et al, 2002) and few participants reported severe levels of drug misuse. Both groups reported an increased level of drug misuse at follow-up, although this was significant only amongst comparator group participants.…”
Section: Alcoholmentioning
confidence: 92%
“…These included a single evaluation of the Broward County, Florida, MHC (20)(21)(22), a multisite study examining the effectiveness of four large, wellestablished MHCs (23), plus two further studies (24,25). All four evaluations employed a quasi-experimental design, although there were some differences in their execution.…”
Section: Mhcs Without Actmentioning
confidence: 99%